Raising Rajas in Hathayoga and Beyond - Westoby, Ruth (Religions of South Asia, 2019)
This article discusses the concept of rajas in the Hathayoga corpus and compares it with material in Ayurveda and Daoism. Rajas is the red blood of menstruation, female sexual fluid, and one aspect of a gendered binary with bindu or semen. In texts deriving from a male celibate context, rajas occurs within male practitioners without the interaction of a woman. In some paradigms of the yogic body, bindu is drawn upwards and preserved alongside rajas using the technique of vajrolimudra, conferring success (siddhi) and immortality (amrta). Women appear infrequently in Hatha texts, but those who preserve their rajas are said to be yoginis. Rajas in Ayurveda functions in embryology as a vital essence, thus explaining its power in Hathayoga. Daoist materials are more detailed and cohesive than Hatha, and female inner alchemy (Nüdan) describes a practice of voluntary amenorrhea, ‘slaying the crimson dragon’—the halting of menstruation. The Daoist model enables an interpretation of the scant Hatha sources to suggest that yoginis who preserve their rajas potentially halt their periods.